Seismic risk in Barquisimeto. Learning from the catastrophe in Turkey (Gaceta Técnica, 2023)
The earthquake that occurred in Turkey on February 6, 2023, although regrettable due to the magnitude of the human and material damage that occurred, provides an opportunity to analyze the state of the art of earthquake-resistant construction in that country, as well as the different actions of government and social organizations committed to the application of regulations to mitigate the damage of these earthquakes. The study presented here of the characteristics of this event and the experience lived at that time by that country, allows to evaluate and compare equally the state of the art in earthquake resistance in the urban axis of the cities Barquisimeto - Cabudare, either in the governmental and social organization, with the purpose of improving the capacity to respond to a seismic event
Keywords: Turkey earthquake; seismic vulnerability; seismic microzoning of Barquisimeto